2009
DOI: 10.1126/science.1174095
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Novel Phenolic Pathway for Pollen Development

Abstract: Metabolic plasticity, which largely relies on the creation of new genes, is an essential feature of plant adaptation and speciation and has led to the evolution of large gene families. A typical example is provided by the diversification of the cytochrome P450 enzymes in plants. We describe here a retroposition, neofunctionalization, and duplication sequence that, via selective and local amino acid replacement, led to the evolution of a novel phenolic pathway in Brassicaceae. This pathway involves a cascade of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 30 publications
4
158
0
1
Order By: Relevance
“…Thus, these genes are likely paralogs, where one gene results from the gene duplication of the other. This is consistent with a theory that explains the evolution of enzyme function (Ober, 2005;Des Marais and Rausher, 2008;Matsuno et al, 2009), which states that a set of enzymes with similar (but different) catalytic functions can be generated by gene duplication. As implicated from the genomic map and the phylogenetic tree (Figure 1), gene duplication of cluster I UGTs appears to have occurred in the grapevine genome, resulting in a small subcluster of functionally differentiated UGTs.…”
Section: Evolution Of Sugar Donor Specificitysupporting
confidence: 73%
“…Thus, these genes are likely paralogs, where one gene results from the gene duplication of the other. This is consistent with a theory that explains the evolution of enzyme function (Ober, 2005;Des Marais and Rausher, 2008;Matsuno et al, 2009), which states that a set of enzymes with similar (but different) catalytic functions can be generated by gene duplication. As implicated from the genomic map and the phylogenetic tree (Figure 1), gene duplication of cluster I UGTs appears to have occurred in the grapevine genome, resulting in a small subcluster of functionally differentiated UGTs.…”
Section: Evolution Of Sugar Donor Specificitysupporting
confidence: 73%
“…Matsuno and co-workers observed that the young members showed, for this family, an unusual lack of intronic sequence and were clustered on chromosome 1. Consequently, it was suggested that the family's expansion was the result of a series of events starting with retrotransposition and tandem duplication, concomitant with neofuntionalization and subsequent further specialization, or broadening of the function [23]. The positions of amino acids under strong positive selection and structure homology modelling indicated enlargement of the substrate access channel and active site cavity in comparison with the ancestral CYP98A.…”
Section: Cyp98a Bridges General and Specialized Phenylpropanoid Metabmentioning
confidence: 99%
“…In line with our observation of the manufacture of a specific set of metabolites in this tissue (Dataset S1), previous studies have shown that metabolites, notably certain phenolic derivatives, are abundant and highly specific for the tapetum (specialized layer of nutritive cells and source of precursors for the pollen coat within anthers) of anthers and pollen grains (39)(40)(41). The biosynthesis of these phenolic derivatives, with potential roles in pollen coat composition and establishment of fertilization barriers, has been linked to rapid metabolic gene evolution through retroposition and neofunctionalization (42). In a cross-species study on transcriptome evolutionary divergence, the fastest rates of gene expression divergence and signatures of transcriptome specialization were detected in anthers, whereas the lowest rates of evolution were detected in roots (43).…”
Section: Cross-tissue Intensity Variationmentioning
confidence: 99%